2018
DOI: 10.1007/s00134-018-5212-y
|View full text |Cite
|
Sign up to set email alerts
|

A state of the art review on optimal practices to prevent, recognize, and manage complications associated with intravascular devices in the critically ill

Abstract: Intravascular catheters are inserted into almost all critically ill patients. This review provides up-to-date insight into available knowledge on epidemiology and diagnosis of complications of central vein and arterial catheters in ICU. It discusses the optimal therapy of catheter-related infections and thrombosis. Prevention of complications is a multidisciplinary task that combines both improvement of the process of care and introduction of new technologies. We emphasize the main component of the prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
116
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(122 citation statements)
references
References 132 publications
(162 reference statements)
0
116
1
5
Order By: Relevance
“…The management of CRBSI, however, is more nuanced with a lot of factors influencing decision‐making. These include identifying the pathogen, the clinical condition of the patient including hemodynamic stability and the immediate availability of an alternative intravenous access . The ongoing need for having a central venous access and familiarity with the use of ALT are also important pointers in the decision for CVC removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of CRBSI, however, is more nuanced with a lot of factors influencing decision‐making. These include identifying the pathogen, the clinical condition of the patient including hemodynamic stability and the immediate availability of an alternative intravenous access . The ongoing need for having a central venous access and familiarity with the use of ALT are also important pointers in the decision for CVC removal.…”
Section: Discussionmentioning
confidence: 99%
“…One of the important mechanisms in the pathogenesis of CRBSI and CC is biofilm formation, a process wherein the microorganisms adhere to the inner surface of CVC and exhibit much higher minimum inhibitory concentrations (MICs) for antibiotics when compared to non‐biofilm related infections . To address this issue, the strategy of antibiotic lock therapy (ALT) was devised to achieve 100–1000‐fold higher MICs in lumen compared to what can be achieved upon systemic administration .…”
Section: Introductionmentioning
confidence: 99%
“…IJV, internal jugular vein puncture angle; OA, overlapping angle (represents part of internal jugular vein's angular width covered by carotid artery artery); SPA, internal jugular vein safe puncture angle (equal to IJV and OA difference). compared with anatomic landmarks, was associated with a greater procedural success, a lower number of attempts, shorter time to catheterize the vessel and a marked reduction of mechanical complications [11]. A Cochrane Database search including 22 randomized controlled trials confirmed that the rate of total complications overall and inadvertent artery puncture decreased by more than 70% when compared with US-guided insertion of IJV catheters with an anatomical landmark technique in both adults and children [8].…”
Section: Parametermentioning
confidence: 93%
“…In the case of severe sepsis or shock, the catheter should be promptly removed. 15,27 However, most of the suspected catheter infections are not life-threatening and diagnostic techniques allowing an accurate diagnosis while keeping the catheter in place are an attractive option 28 (see "Management of Catheter-Related Infections" section).…”
Section: Diagnosis Of Cr-bsi With Catheter In Placementioning
confidence: 99%